Підсумки інтродукції видів роду Pinus L. на Нижньодніпровських Пісках - Shlapak, V.P. (M.M. Gryshko National Botanical Garden of the NAS of Ukraine, 2002)
Totals of afforestation of mobile Lower-Dnipro sandy tracts by 18 introduced species of genus Pinus L. and processes of forming of sandy relief and its overgrown by vegetation are viewed. Most perspective for afforestation of mobile sandy tracts species of genus Pinus L. in the south of Ukraine are picked out.